ANALISIS PENERAPAN MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK - Rieke Pernamasari; Syifa Nur Rahmawati (Unversitas Prof. Dr. Moestopo (Beragama), 2021)
Changes or modernization of the tax administration system is one of the government’s efforts in improving taxpayer compliance. Changes made covering the areas of organizational structure, business processes and information technology and communications, human resource management, and implementation of good governance. The purpose of this study was to determine the influence of modernization of the tax administration system onindividual taxpayer complience (Survey on the taxpayer in KPP Pratama Jakarta Kembangan). Data were obtained from 100 respondents listed as individual taxpayer in KPP Pratama Jakarta Kembangan. This study tested using multiply liniear regression analysis. The result of the research shows variables organizational structure and implementation of good governance have a significant effect on individual taxpayer compliance. Variables business processes and information technology and communications, and human resource management have not a significant effect on individual taxpayer compliance in the Tax Office (KPP) Pratama Jakarta Kembangan.